The Adoption of ChatGPT - Anders Humlum; Emilie Vestergaard (Institute of Labor Economics (IZA), 2024)
We study the adoption of ChatGPT, the icon of Generative AI, using a large-scale survey experiment linked to comprehensive register data in Denmark. Surveying 100,000 workers from 11 exposed occupations, we document ChatGPT is pervasive: half of workers have used it, with younger, less experienced, higher-achieving, and especially male workers leading the curve. Why have some workers adopted ChatGPT, and others not? Workers see a substantial productivity potential in ChatGPT but are often hindered by employer restrictions and required training. Informing workers about expert assessments of ChatGPT shifts workers' beliefs and intentions but has limited impacts on actual adoption.
Keywords: J24; O33; 330; technology adoption; labor productivity